The Effect of Stevia (Stevia rebaudiana Bertoni) Leaf Extract Cream on Transforming Growth Factor-β1 Levels and Collagen Amount in the Skin of Male Wistar Rats (Rattus norvegicus) Exposed to Ultraviolet B - Febrina, Jessica; Muliarta, I Made; Wahyuniari, Ida Ayu Ika; Sumadi, I Wayan Juli; Linawati, Ni Made; Artini, I Gusti Ayu (Bogor Agricultural University, Indonesia, 2026)
Ultraviolet B (UVB) exposure is a major cause of skin aging, leading to collagen degradation and wrinkles due to free radical damage. Stevia (Stevia rebaudiana Bertoni) has antioxidant properties that may counteract this by preserving Transforming Growth Factor-β1 (TGF-β1), essential for collagen synthesis. This study evaluated the effects of stevia leaf extract cream on TGF-β1 and collagen levels in male Wistar rats. Thirty rats were divided into five groups: K0 (no UVB, no cream), K1 (base cream), P1 (2.5% stevia cream), P2 (5% stevia cream), and P3 (10% stevia cream). Groups K1, P1, P2, and P3 were exposed to a cumulative UVB exposure of 840 mJ/cm2 over four weeks. The TGF-β1 levels measured by ELISA did not differ significantly among groups (p>0.05). However, collagen levels, assessed using Picro Sirius Red staining, varied significantly (p<0.05). The K1 exhibited significantly lower collagen compared to K0 (p=0.003), whereas the P2 group effectively prevented collagen degradation compared to K1 (K1: 65.87% vs. P2: 77.92%; p = 0.005). While stevia leaf extract cream did not prevent TGF-β1 reduction, it demonstrated a clear protective effect against UVB-induced collagen loss. Among the tested concentrations, 5% stevia leaf extract cream was the most effective in preserving dermal Collagen, highlighting its potential as a topical agent for preventing photoaging and maintaining skin structural integrity.